Antibodies to receptor activator of nuclear factor-κ B ligand (RANKL) - Terpos, E.; Christoulas, D.; Dimopoulos, M.-A. (Expert Opinion on Therapeutic Patents, 2008)
Patent WO02095012A1 claims for the development of antibodies against receptor activator of nuclear factor-κ B ligand (RANKL) and immunologically functional fragments that neutralize RANKL. These molecules can be used to detect RANKL in biological samples, allowing the identification of pathological conditions in which RANKL alteration contributes to their pathophysiology. The use of anti-RANKL antibodies is of high importance in the treatment of bone disorders characterized by the stimulation of osteoclast function and subsequent bone loss. Postmenopausal and steroid-induced osteoporosis, myeloma bone disease, cancer bone metastases with lytic lesions and bone loss due to rheumatoid disorders (including rheumatoid arthritis) are candidates for anti-RANKL therapy, as RANKL is implicated in their pathogenesis. © 2008 Informa UK Ltd.
Keywords: B ligand (RANKL); Bone formation; Bone metastasis; multiple myeloma; Osteoporosis; Receptor activator of nuclear factor-κ; Rheumatoid arthritis